Peran Kewarganegaraan dalam Hukum Humaniter Internasional : Perlindungan terhadap Kombatan dan Non-Kombatan - Ahmad Muhamad Mustain Nasoha; Iswatun Khasanah; Syaira Nadhifa Aushaf; Ismi Nur Hidayah; Ashfiya Nur Atqiya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The regulation of protection during armed conflicts is greatly aided by the distinction between the rights and protections granted to combatants and non-combatants under International Humanitarian Law (IHL). Nonetheless, there hasn't been much discussion in the literature about how nationality affects how these legal safeguards are applied. This study attempts to investigate how fighters' and non-combatants' rights and safeguards under IHL are impacted by nationality. The results show that nationality can have a substantial impact on the legal status and level of protection that individuals receive, regardless of whether they are combatants or not. This research examines obstacles to the application of legal safeguards and illustrates how nationality influences their implementation using case studies of the crises in Syria and Ukraine. The study suggests that within IHL, precise standards on nationality be developed.